TEKNIK PSIKODRAMA DALAM BIMBINGAN KELOMPOK UNTUK MENGATASI PERILAKU MEROKOK SISWA SMA - Cici Febrianti; Rima Irmayanti (FOKUS (Kajian Bimbingan & Konseling dalam Pendidikan), 2019)
Smoking behavior is one form of juvenile delinquency in the school environment. In dealing with smoking behavior high school students can be done through group counseling services with psychodrama techniques. The purpose of this paper is to determine the effect of group guidance with psychodrama techniques as a school effort to address student smoking behavior. The method used is the literature method. Based on the results of a literature review from various sources and previous research shows that group guidance with psychodrama techniques is considered effective to overcome the smoking behavior of high school students. Keywords: Group Guidance, Psychodrama Technique, Smoking Behavior.